HARMONI PREDATOR DAN MANGSA - Limbong, Sukanto (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2024)
This research examines the application of the concept of peace in Isaiah 11:6-8 to foster interfaith reconciliation in Indonesia, which faces various religious conflicts. The subjects of the study include the symbolism in the biblical text and its application in a modern context. The aim of the research is to explore the theological meaning of the text and its relevance in creating harmony among religious groups. The research employs hermeneutics and literature study methods to analyze the meaning of the text. Data collection techniques involve analyzing historical context, text structure, and theological perspectives. The findings reveal that the symbolism of predator and prey illustrates the potential for reconciliation and harmony that can be applied to address religious conflicts. The conclusion emphasizes that the message of peace in Isaiah 11:6-8 is highly relevant and can serve as a foundation for reconciliation initiatives, significantly contributing to theological studies and peace practices in a multicultural society.